Utilization of a novel patient-specific 3D-printing template for percutaneous endoscopic transforaminal discectomy: results from a randomized controlled trial - Xin Huang; Qipeng Luo; Chen Liang; Yixuan Wang; Donglin Jia; Shuiqing Li; Xiangyang Guo (Frontiers in Neuroscience, 2024)
BackgroundThe learning curve for percutaneous endoscopic transforaminal discectomy (PETD) is steep, especially for the puncturing and localization procedures. The implementation of 3D printing technology may solve this problem.MethodsA novel individualized 3D-printing template (3D-PT) was designed and utilized in PETD. A prospective randomized controlled trial was performed. A total of 28 patients with lumbar disc herniation treated with PETD were analyzed. Of these, 14 patients were treated with the assistance of 3D printing technology (3D-PT group) in conjunction with fluoroscopy, while the remaining 14 patients were treated exclusively under the guidance of C-arm fluoroscopy (control group).ResultsThe number of puncture attempts in the 3D-PT group was significantly less than in the control group (1.36 ± 0.63 vs. 6.07 ± 3.08, p = 0.000). The 3D-PT group exhibited a significant reduction in both intraoperative puncture fluoroscopies (2.71 ± 1.27 vs. 12.14 ± 6.15, p = 0.000) and the overall number of fluoroscopies (2.71 ± 1.27 vs. 17.43 ± 6.27, p = 0.000). In the 3D-PT group, there was a significant reduction in both the puncture time (5.77 ± 1.82 vs. 13.99 ± 4.36, p = 0.000) and the total operation time (60.39 ± 9.78 vs. 76.25 ± 17.78, p = 0.007). Complications were not observed in either group.ConclusionThe application of the novel individualized 3D-PT for PETD is effective and safe. The technique has substantial potential and is worth widely promoting.